2013
DOI: 10.1080/14733285.2013.829660
|View full text |Cite
|
Sign up to set email alerts
|

Is domestic work aworst formof child labour? The findings of a six-country study of the psychosocial effects of child domestic work

Abstract: In this paper, we report on a study of the psychosocial effects of child domestic work (CDW) in six countries and the relevance of our findings to international legislation. Our results suggest that CDW is highly heterogeneous. While some young child domestic workers work long hours, suffer physical punishment and are at risk of psychosocial harm, others are able to attend school and benefit from good relationships with their employers and networks of support. Child domestic workers in India and Togo were most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 13 publications
2
46
0
2
Order By: Relevance
“…Levison and Langer focused on children working as domestic servants a common occupation for girls in some countries, in six countries in the WHO region of the Americas—Argentina, Brazil, Chile, and Colombia in South America and Costa Rica and Mexico in Central America—and suggested they were sometimes better off than nondomestic servant child laborers with respect to increased school enrollment [ 56 ]. Gamlin et al surveyed over 3000 children, nearly half involved in domestic work, to examine physical exposures and psychological effects of such work in six countries spanning four WHO regions—Peru, Costa Rica, Tanzania, Togo, India, and the Philippines—with the most associated S&H risks reported in India and Togo [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Levison and Langer focused on children working as domestic servants a common occupation for girls in some countries, in six countries in the WHO region of the Americas—Argentina, Brazil, Chile, and Colombia in South America and Costa Rica and Mexico in Central America—and suggested they were sometimes better off than nondomestic servant child laborers with respect to increased school enrollment [ 56 ]. Gamlin et al surveyed over 3000 children, nearly half involved in domestic work, to examine physical exposures and psychological effects of such work in six countries spanning four WHO regions—Peru, Costa Rica, Tanzania, Togo, India, and the Philippines—with the most associated S&H risks reported in India and Togo [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ILO and others have highlighted the vulnerabilities of child domestic workers and the risks they routinely face: long and tiring workdays; exposure to toxic chemicals; carrying heavy loads; using dangerous tools such as knives, axes, and hot pans; inadequate rest, food, or accommodations; and the possibility of physical, verbal, and sexual violence (Blagbrough & Glynn, ) . Researchers who examined data from six countries so that they could ascertain whether domestic work could be accepted as a worst form of child labor due to its psychosocial effects found that children in India and Togo were the most at risk (Gamlin, Camacho, Ong, & Hesketh, ). Research has also shown that many of the children are unpaid, for example, 65% of them in Togo and 94% of them in Costa Rico (Gamlin et al, , p. 218).…”
Section: Labor Aspects Of Child Marriagementioning
confidence: 99%
“…Researchers who examined data from six countries so that they could ascertain whether domestic work could be accepted as a worst form of child labor due to its psychosocial effects found that children in India and Togo were the most at risk (Gamlin, Camacho, Ong, & Hesketh, ). Research has also shown that many of the children are unpaid, for example, 65% of them in Togo and 94% of them in Costa Rico (Gamlin et al, , p. 218). While recognizing the variation in the conditions of work for child domestic workers around the world, most scholars agree that they need adequate protection from abusive working conditions, and that in some cases, child domestic work is a worst form of child labor.…”
Section: Labor Aspects Of Child Marriagementioning
confidence: 99%
“…Even where there are regulations to protect child domestic workers, it is extremely difficult to enforce because the workplace is a private dwelling, effectively giving the employer total control over the person in their ‗service'. Thus, though it is clear that domestic workers are uniquely vulnerable, the degree of harm to which they are exposed is not clear due to its hidden nature (Jennie et al, 2015). In spite of this difficulty, exploitations reported by previous studies include low salaries, excessive domestic duties, long hours of work, limited freedom of movement, insecure accommodation and lack of privacy (Black, 2002).…”
Section: Introductionmentioning
confidence: 99%